THE CHOICE OF ANTIMICROBIAL THERAPY AMONG PHYSICIANS IN THE TREATMENT OF GESTATIONAL PYELONEPHRITIS - Natalya Chuhareva; Roman Bontsevich; Kristina Shchurovskaya; A. Lysenko (Belgorod National Research University, 2016)
From 1 to 10% of the physiological pregnancy complicated by acute pyelonephritis. The purpose work- analyze the choice of antimicrobial therapy among physicians in the treatment of gestational pyelonephritis. Materials and methods-analysis of the anonymous survey in the framework of the second stage of the All-Russian pharmacoepidemiological study, "Epidemiology of the use of drugs in pregnant women", which was conducted from February to April 2015. On the basis of this was carried out to compare the results with the results of the survey of doctors of the Belgorod region. Results and discussion. Approximately half of the doctors choose the treatment of pyelonephritis in pregnant cephalosporins of generations II and III, as well as amoxicillin / clavulanate. Up to 30% of physicians prescribe ineffective in this case macrolides. A third of doctors sent patients for treatment to other specialists. Conclusion. An analysis of the responses of doctors tactics purpose of antimicrobial therapy in gestational pyelonephritis showed that only half of practitioners prescribed therapy based on the rational use of antimicrobials.